Peranan sekolah dan GUN dalam pembangunan nilai pelajar menerusi penerapan nilai murni: satu sorotan - Mohamad Khairi Othman ,; Asmawati Suhid, (Universiti Kebangsaan Malaysia, 2010)
Social and disciplinary problems among school students is of growing concern among Malaysian educationist. The school administration and teachers are more influential in handling these problems compared to other parties in the society as the students receive their knowledge in a formal and systematic way. At school the teachers show them how to be a good and cultured person. This paper discusses and elaborates this issue based on Veugelers (2000). According to Veugelers, the type of school, school culture, teacher personality, teachers teaching experiences will influence the development of the students’ values.